2001
DOI: 10.2172/15000240
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamics Experiment Phase VI: Wind Tunnel Test Configurations and Available Data Campaigns

Abstract: and Bob Kufeld helped us understand the challenges of converting our field measurement turbine to a wind tunnel model. Thanks also to Bob Kufeld for rotating through our data collection stations to give us a break. Thanks to Janet Beegle and Joe Sacco for coordinating NASA resources. Thanks to David Nishikawa for incorporating last-minute changes to the NASA file format. Art Silva and Ben Bailey kept all the NASA instrumentation operating smoothly. Rob Fong continued to troubleshoot the balance scales until th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
629
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(708 citation statements)
references
References 12 publications
19
629
1
8
Order By: Relevance
“…This two bladed wind turbine of 10 m diameter and of airfoil section of S809 has been tested in the wind tunnel of NASA at Ames [14]. These experiments contain a database for analysis of aerodynamic properties of wind turbine.…”
Section: Analysis Of Normal and Tangential Forcesmentioning
confidence: 99%
“…This two bladed wind turbine of 10 m diameter and of airfoil section of S809 has been tested in the wind tunnel of NASA at Ames [14]. These experiments contain a database for analysis of aerodynamic properties of wind turbine.…”
Section: Analysis Of Normal and Tangential Forcesmentioning
confidence: 99%
“…One possibility for increasing the barge-pitch damping through active pitch-to-stall control is to tailor the airfoildata coefficients so that rotor thrust increases more with wind speed in Region 3 than what resulted with the existing airfoils. Experimental data from NREL's Phase VI Unsteady Aerodynamics Experiment (UAE), 13 which tested a passive stall-regulated wind turbine in the National Full-Scale Aerodynamics Complex at the National Aeronautics and Space Administration (NASA) Ames Research Center, showed a nearly steady increase in rotor thrust with wind speed from cut-in to cut-out. This would translate into a nearly constant steady-state thrust sensitivity to wind speed, T V ∂ ∂ , across all wind speeds for the UAE wind turbine.…”
Section: B Active Pitch-to-stall Speed-control Regulationmentioning
confidence: 99%
“…Soerensen and Hansen (1998) solved the Reynoldsaveraged Navier-Stokes (RANS) equations and applied the Menter shear stress transport (SST) k − ω turbulence model to a full-scale wind turbine. In 2002 the National Renewable Energy Laboratory (NREL) performed the Unsteady Aerodynamic Experiment (UAE) (Hand et al, 2001), which has long been the reference for several CFD computations. For example, Johansen et al (2002) presented a detached eddy simulation (DES) on the NREL UAE phase VI blade to demonstrate the capabilities of predicting flow separation.…”
Section: Introductionmentioning
confidence: 99%